Two new species of freshwater ostracods (Crustacea: Ostracoda) from the northeast of Thailand, with notes on sexually reproducing populations of Chrissia and Strandesia - Savatenalinton, Sukonthip (Zootaxa, 2025)
Two new species of freshwater ostracods (Chrissia ueluenakarati sp. nov. and Strandesia buengkanensis sp. nov.) were discovered from a marshy area next to a weir in Bueng Kan Province, northeast Thailand, and the descriptions are provided here. Both were sexual populations and thus reproductive organs were compared within their genera. Chrissia ueluenakarati sp. nov. is the first sexual population of the genus in Southeast Asia. Chrissia species with sexual populations are also listed here. Strandesia buengkanensis sp. nov. belongs to a group with S. kraepelini (Müller, 1906) and S. karanovicae Savatenalinton, 2024, based on the absence of the subapical dorsal seta on the first segment of the antennule, which is endemic to Southeast Asia. A list of the species of Strandesia recorded in Southeast Asia is provided with indications of sexual populations. The presence of the new species in the present contribution, together with previous records, are evidence illustrating the high diversity of the Thai ostracod fauna.